2020
DOI: 10.1101/2020.06.09.20124008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An imperfect tool: contact tracing could provide valuable reductions in COVID-19 transmission if good adherence can be achieved and maintained

Abstract: Background: Following a consistent decline in COVID-19-related deaths in the UK throughout May 2020, it is recognised that contact tracing will be vital to relaxing physical distancing measures. The increasingly evident role of asymptomatic and pre-symptomatic transmission means testing is central to control, but test sensitivity estimates are as low as 65%. Methods: We extend an existing UK-focused branching process model for contact tracing, adding diagnostic testing and refining parameter estimates to demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 50 publications
5
22
0
Order By: Relevance
“…Our findings that contact tracing and isolation are unlikely to be effective on their own in suppressing the SARS-CoV-2 epidemic are consistent with those of other models 22,58,59 . The contribution of contact tracing and isolation in our model was most significant when global contact reductions were 40-70% of their usual levels, under which growth was not suppressed and over which very few epidemics took off (contingent on the parameters of transmission that we chose).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings that contact tracing and isolation are unlikely to be effective on their own in suppressing the SARS-CoV-2 epidemic are consistent with those of other models 22,58,59 . The contribution of contact tracing and isolation in our model was most significant when global contact reductions were 40-70% of their usual levels, under which growth was not suppressed and over which very few epidemics took off (contingent on the parameters of transmission that we chose).…”
Section: Discussionsupporting
confidence: 91%
“…The effects of non-uptake or of partial adherence on epidemic growth will depend on the dynamics of within-household transmission, making this important to capture in modelling. There might also be practical trade-offs since a strict system that in theory might be most effective in reducing transmission could result in lower adherence; and there are complications to releasing contacts who test negative early due to low test sensitivity 22 . While there is evidence that the average number of contacts made at the beginning of the UK's 'lockdown' at the end of March 2020 was reduced by over 70% 23 compared to a 2006 contact survey 14 , another survey from two days in early May 2020 found that almost three quarters of individuals who showed or whose household showed SARS-CoV-2 symptoms had left the house in the previous 24 hours, behaviour that was contrary to policy at the time 24 .…”
Section: Introductionmentioning
confidence: 99%
“…One potential mechanism of regaining control is to introduce a short period of intense measures to substantially reduce cases — this has been dubbed a ‘circuit breaker’ although “precautionary break” is a more apposite name. It is hoped that by driving infections to a sufficiently low level, other measures such as test-trace-and-isolate will have greater capacity to prevent the spread of infection [11]. In common with other resource limited controls [12], we expect test-trace-and-isolate to be most effective when the level of infection is relatively low [13].…”
Section: Introductionmentioning
confidence: 99%
“…In that study, resurgence was said to have occurred when the number of individuals who are symptomatic infectious reached 100. Other studies have also defined ‘large outbreaks’ as those in which a threshold number of cases is exceeded [ 88 , 89 ]. However, while threshold values were reported clearly in all these studies, we emphasize that the precise type of threshold and the value used should be chosen according to practical relevance in the particular scenario under consideration.…”
Section: Discussionmentioning
confidence: 99%